2013
DOI: 10.1097/ta.0b013e3182a74a3f
|View full text |Cite
|
Sign up to set email alerts
|

Burden of hospitalizations for bicycling injuries by motor vehicle involvement

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
(10 reference statements)
2
21
1
3
Order By: Relevance
“…The main mechanism leading to death is the development of multiple organ failure (MOF) despite progress of intensive care management of patients [1]. Management of patients is linked with huge hospitalization costs due to the occupancy of beds in Intensive Care Units (ICUs) of tertiary hospitals [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism leading to death is the development of multiple organ failure (MOF) despite progress of intensive care management of patients [1]. Management of patients is linked with huge hospitalization costs due to the occupancy of beds in Intensive Care Units (ICUs) of tertiary hospitals [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-fifth (19.3%) of the injured patients were elderly, and male sex was predominant (75.2%) [5, 13, 14]. Although we did not include pediatric and adolescent patients (<20 years), many previous studies demonstrated that pediatric and elderly patients were vulnerable to bicycle injuries and prone to fatal outcomes [5, 7, 8, 13, 15–17]. In our study, the overall proportion of serious outcomes decreased during the study period, but elderly patients consistently had a higher frequency of serious outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mainstay of injury prevention approaches is public education and legislation, as well as the design and implementation of a bicycle-specific infrastructure [7, 8, 13, 18, 21]. Controversy over whether bicycle helmet legislation deters bicycle riders persists despite a lack of strong evidence; however, studies with improved designs have indicated that bicycle helmet legislation is a non-factor, but rather a lack of infrastructure or concern for safety are the main deterrents of riding a bicycle [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Bicycle‐related fatalities are more likely to be because of head injuries, with one report that 70% of bicycle‐related fatalities are associated with head injuries . The wearing of helmets was made mandatory across all Australian jurisdictions between 1990 and 1992 and the law is referenced in the Australian Road Rules .…”
Section: Introductionmentioning
confidence: 99%